(untitled) (Música Hodie, 2018)
In this article, an analysis of the piece Desdobramentos do contínuo for violoncello and live-electronics is addressed concerning instrumental extended techniques, electroacoustic tape sounds, real-time processing, and their interaction. This is part of a broad research about the computer-aided musical analysis of electroacoustic mu- sic. The objective of the analysis of this piece is to understand the spectral activity of the emergent sound structures, in terms of which events produce huge timbre variations, and to identify timbre subtle nuances that are not percep- tible on a first listen of the work. We conclude comparing the analyses results to the compositional hypotheses pre- sented in the initial sections.